Kajian 1 Petrus 5:2-3 Tentang Tugas Gembala Jemaat - Eveline, Sjanette; Engelia Horman, Agnes (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2024)
There are many ways to maintain a group of people in a formal or informal organization for a specific purpose. This is also done in a group of believers called a church. In the church there is a term shepherding. Shepherding is a very important thing in the spiritual growth of the congregation, where the role is a pastor who must give his life truly according to his calling in devotion to God. This, as explained in 1 Peter 5:2-3, must be done voluntarily, without coercion, because the service must be sincere and pure, so that it can have an impact through example.